Pendampingan Pembelajaran Jarak Jauh (PJJ) bagi Siswa Madrasah Ibtidaiyah (MI) Nurul Himmah Desa Andong, Boyolali - Desi Anggi Ramadhani; Azzah Nilawaty (Transformatif : Jurnal Pengabdian Masyarakat, 2021)
The pandemic of Covid-19 that hit Indonesia makes changes in all sectors, especially in education. All levels of education in Indonesia are experiencing changes in the learning system.  Long Distance Learning (PJJ) or online learning is an alternative for the educational system through service activities and research carried out by students using direct observation methods.  Observation methods are done in the communities by interviews, documentations and analysis of problems faced by the community in educational problems. The service carried out in Duwet, Andong, Andong, Boyolali leads to the Mentoring of long-distance learning Program (PJJ) for Nurul Himmah Islamic Elementary School (MI) students.  The results of the study show that there are still many obstacles experienced by children during the implementation of the long-distance Learning Mentoring (PJJ) such as students' lack of understanding about the taught material, the number of assignments teacher gives, wasteful quotas, and parents who cannot accompany and do not understand the long-distance Learning material. As a solution to the problems of the long-distance learning, the researchers create a long-distance Learning Mentoring Program for students of grades V and VI.  This program has a positive impact for the students and the parents in overcoming the obstacles of the long-distance learning.